Implementasi Modul Ajar Bermuatan Coding Tema Alam Semesta Sub Tema Bintang Anak Usia 5-6 Tahun Di TKN Ubedolumolo - Oka, Gde Putu Arya; sulastri (STKIP CITRA BAKTI, 2024)
This study aims (1) to determine the effectiveness of the teaching module containing coding on the theme of the universe with a sub-theme of stars for children aged 5-6 years at TKN Ubedolumolo. (2) to continue the previous research entitled development of a teaching module containing coding on the theme of the universe with a sub-theme of stars for children aged 5-6 years by Raymunda Nona Tuga (RN Tuga, GPA Oka & KD Dhiu, 2022). The type of research is descriptive qualitative while the evaluation model used uses the Donal Kirkpatrick model, four levels of evaluation including: 1) reaction, 2) learning, 3) behavior, 4) results. The data collection method used is the interactive method of Miles and Huberman.Research results: At level one, children's reactions obtained 50% results in the category (very effective), at level two the learning process obtained results at 80% (very effective), at level three behavior obtained results at 66% (very effective), and at level four children's learning results obtained 66% results (very effective). Keywords: Teaching Module; universe coding; stars